Zależność funduszu rozwoju od wyniku finansowego w przedsiębiorstwie zarządzanym centralnie - Czerwińska, Elżbieta (Wydział Prawa i Administracji UAM, 1968)
The progress fund in an enterprise arises from inflows, the amount of which depends on the enterprise's financial result. These inflows may come from the enterprise's profit or from subsidy. The ratio of these inflows to the financial result, as well as the sources of the inflows are determined by financial regulations and depend on whether high profit, low profit or deficit is assumed in the enterprise's plan. These regulations were subject to several changes between 1958 and 1967. It is interesting to investigate, how inflows to the progress fund were related to the financial result by force of the successive regulations. According to the 1958 regulations there was a constant ratio between profit (or, if the enterprise planned losses, between turnover) and inflow to the progress fund. This ratio was predetermined by the enterprise's plan individually for every enterprise. The implementation of the plan had no influence on this ratio. The regulations were such that it was convenient for the enterprise to plan its profit (or its turnover) as low as possible. The characteristic feature of the regulations in force between 1959 and 1965 was the regression of inflows to the progress fund when the enterprise's financial result was better than planned. The greater was the profit (or smaller the loss) compared wit planned quotas, the relatively smaller was the inflow to the progress fund. Planning of unrealistically low profit ceased ot be attractive from the point of view of the progress fund. The system of regression in force between 1959 and 1965 had one rather great defect. The improvement of enterprise's planned financial result between 40 and 60 per cent did not cause any increase of the inflow to the progress fund, and in some intervals it even caused decrease of the inflow. The regulations in force since 1966 have removed regression of inflows to the progress fund. The constant ratio between profit and contributions to the progress fund has been reintroduced as far as enterprise planning high profit are concerned. Enterprises planning low profit or deficit know inflows to their progress fund only in case their financial result is not better than planned. They do not know at all whether they have the right — and if so to what extent — to transfer any additional amount to the progress fund, if they achieve better results than they had planned. The additional inflow becomes something like extra subsidy, granted arbitrarily to the enterprise by the board of the association of enterprises. Therefore no defifnite relation exists between inflow to the progress fund and the financial result in the last two groups of enterprises.
The Dependence of the Progress Fund on the Financial Result a State Enterprise